Third International Conference on Natural Computation (ICNC 2007) 2007
DOI: 10.1109/icnc.2007.455
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Evaluation Using Fuzzy Approach

Abstract: Likert-type scale that employs ordinal values to represent linguistics terms has been very popular in the studies on job satisfaction evaluation. In this work, it is argued that the use of ordinal values in Likert scale does not offer the best way in representing the linguistic terms. This paper proposes the use of fuzzy sets to represent linguistic terms in Likert-type scale and employs the technique using fuzzy conjoint method in job satisfaction evaluation. Experimental results show that the analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Azadeh et al (2006) O ? Rasmani and Shahari (2007) O O O Calisir and Gumussoy (2007) O O ? Mohammad Fam et al (2007) O ?…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Azadeh et al (2006) O ? Rasmani and Shahari (2007) O O O Calisir and Gumussoy (2007) O O ? Mohammad Fam et al (2007) O ?…”
Section: Resultsmentioning
confidence: 98%
“…Likert-type scale that employs ordinal values to represent linguistics terms has been very popular in the studies related to job satisfaction evaluation. Rasmani and Shahari (2007) showed that the ordinal values in Likert scale does not offer the best way in representing the linguistic terms. They proposed the use of fuzzy sets to represent linguistic terms in Likert-type scale.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Calisir and Gumussoy (2007) used an analysis to assess the impact of IT professionals' demographic features, work stress and work characteristics on job satisfaction. Rasmani and Shahari (2007) proposed the use of fuzzy sets to exhibit linguistic terms in Likert-type scale. They also employed the fuzzy conjoint method in job satisfaction assessment.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…where ( , ) j R y A is the fuzzy set calculated on the basis of responses given by respondents, and ( , ) j F x l is the standard fuzzy set defined for linguistic label l. This similarity measure was used by [8] to evaluate job satisfaction; by [21] to evaluate software usability; by [7] to measure student expectations and by [4] to measure teacher beliefs on learning mathematics. Wang [9] introduced similarity between two fuzzy sets, R and F, based on Set-Theoretic approach as follows:…”
Section: Fuzzy Similarity Measure Used In Fcmmentioning
confidence: 99%
“…Thus, some values from the interval 0-1 with some tolerance zones are assigned to each linguistic term. Currently, in FCM, each linguistic term is expected to be represented by discrete fuzzy sets (see for examples: [3][4][5][6][7][8]). It can be observed that little effort has been made to utilise continuous fuzzy sets in the FCM process although it is expected that the use of continuous fuzzy sets may result in different decision outcomes.…”
Section: Introductionmentioning
confidence: 99%